Lower platelet counts and antiplatelet therapy independently predict better outcomes in patients with head and neck squamous cell carcinoma: a retrospective analysis. Issue 1 (December 2015) - Furlan, Carlo; Steffan, Agostino; Polesel, Jerry; Trovo, Marco; Gobitti, Carlo; Vaccher, Emanuela; Serraino, Diego; Barzan, Luigi; Franchin, Giovanni
Abstract The paper by Rachidiet al. suggests that antiplatelet drugs may play a role in ameliorating the clinical outcome in a large series of patients with head and neck cancer managed with either surgery or radiation. Our data, as well as confirming the results observed by the authors, enhance their clinical relevance pointing out the effect of antiplatelet drugs in terms of locoregional control in the setting of patients with advanced head and neck cancer managed with definitive chemo-radiotherapy.